A source code based model to generate GUI: GUI generation based on source code with declarative language extensions - Monteiro, Marco (2008)
Due to data-driven application nature and its increasing complexity, developing its user interface can be a repetitive and time-consuming activity. Consequently, developers tend to focus more on the user interface aspects and less on business related code. In this paper, we present an alternative approach to graphical user interface development for data-driven applications, where the key concept is the generation of concrete graphical user interface from a source code based model. The model includes the original source code metadata and non-intrusive declarative language extensions that describes the user interface structure. Some Object Relational Mapping tools already use a similar concept to handle interoperability between the data layer and the business layer. Our approach applies the same concept to handle business and presentation layer interoperability. Also, concrete user interface implementation will be delegated to specialized software packages, developed by external entities, that provide complete graphical user interfaces services to the application. When applying our approach, we expect faster graphical user interface development, allowing developers to refocus on the source code and concentrate their efforts on application core logic.